Effect of black rice husk ash on the physical and rheological properties of bitumen - Romastarika, R. (American Institute of Physics Inc., 2017)
Black rice husk ash (BRHA) waste product is inexpensive and can be obtained from rice mills. Reuse of waste product is ideal to reduce pollution, because disposal is decreased or eliminated. The commercial value of BRHA has increased, and it is suitable for use in road construction. In this study, BRHA waste was ground using a grinding ball mill for 120 min to form fine powder. BRHA was then sieved to less than 75 μm. At the laboratory, BRHA was mixed with bitumen to replace 2, 4, and 6 of the total weight, whereas 0 represented the control sample. The penetration, softening point, dynamic shear rheometer (DSR) and rolling thin film oven (RTFO) were investigated in this study. Results showed that bitumen became harder, whereas the rate of penetration decreased when the replacement amount of BRHA increased. Softening point test of bitumen also revealed an increase. The short-term aging test revealed that modification of bitumen could relieve the effect of aging. BRHA waste added into bitumen improved the performance of bitumen. Therefore, the usage of BRHA could help improve the performance of road pavement and reduce the rutting effect. © 2017 Author(s).